THE CONTRUCTION AND WHITE STANDARS OF BEAUTY OF AFRICAN AMERICAN WOMENS SELF-IMAGE - Assagaf, Mokhsen (MAGISTRA, 2004)
African American women have long suffered discriminating actions both as blacks and as women. During the period of slavery, many African women were victims of sexual harassement at the hands of their white masters. When slavery was abolished, mainstream white society created negative stereotypes of African American people to maintain their superiorty. The widely spread stereotypical figures of African American were means used to devalue African American womens status and honor. White society has implanted the negative image of African American women so persistently that many of them believed in their inferiority. In addition to the destructive stereotyping, the dominant white culture also created a racist standards of beauty blue eyes, blonde hair, and white skin. The standard excluded most African American women. With the assumption that Toni Morrisons The Blues Eye portray the intricate life of African American women in the late 1930s and early 1940s, this work is explored to discuss the power of mainstream society in contructing images of beauty and in shaping the self-perception of African American women. In The Blues Eye, Toni Morisson describes a tragic scene when an African American gril named Pecola, who desperately yearn for blues eyes, at last goes insane. Implied in the black girls wish for blues eyes was self-hatred and low self-esteem. Other incidents experienced by other female characters In this novel portray the impacts of prevalent perception of beauty on how these women perceive themselves. This paper attempts to releal the damage caused by the white racist standards of beauty on the psyche of African American.